2011
DOI: 10.1371/journal.pone.0021490
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter concisus and Other Campylobacter Species in Colonic Biopsies from Adults with Ulcerative Colitis

Abstract: IntroductionThe critical role of bacteria in the pathogenesis of ulcerative colitis (UC) is well recognized, but an individual causative microorganism has not been singled out so far. Campylobacter concisus and other non-jejuni species of Campylobacter have been implicated as putative aetiological agents in inflammatory bowel disease in children, but such studies have not been addressed in adults. This study investigated the prevalence of Campylobacter species in colonic biopsy samples from adults with UC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
107
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 39 publications
6
107
2
2
Order By: Relevance
“…6 Mukhopadhya et al, among others, showed a significantly higher incidence of C. concisus in tissue biopsies of the colon in adult patients with ulcerative colitis compared to the control group. 35 Mahendran et al obtained similar results by examining adult patients with Crohn's disease. 6 It has also been shown that certain strains of C. concisus have the ability to colonize the gastrointestinal tract in mice, and can cause weight loss and the formation of liver micro-abscesses.…”
mentioning
confidence: 74%
“…6 Mukhopadhya et al, among others, showed a significantly higher incidence of C. concisus in tissue biopsies of the colon in adult patients with ulcerative colitis compared to the control group. 35 Mahendran et al obtained similar results by examining adult patients with Crohn's disease. 6 It has also been shown that certain strains of C. concisus have the ability to colonize the gastrointestinal tract in mice, and can cause weight loss and the formation of liver micro-abscesses.…”
mentioning
confidence: 74%
“…Similarly, the prevalence of C. concisus was reported to be higher in patients with UC (91)(92)(93)(94). For example, Mahendran and colleagues found a higher prevalence of C. concisus, not only in colonic biopsy specimens from adult CD patients (53%; 8/15 patients) but also in those from UC patients (31%; 4/13 patients), than in controls (18%; 6/33 individuals) (P Ͻ 0.05) (91).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 93%
“…For example, Mahendran and colleagues found a higher prevalence of C. concisus, not only in colonic biopsy specimens from adult CD patients (53%; 8/15 patients) but also in those from UC patients (31%; 4/13 patients), than in controls (18%; 6/33 individuals) (P Ͻ 0.05) (91). Two further studies, conducted in Scotland, showed an increased prevalence of C. concisus DNA in both adults and children presenting with UC (92,93). The first study isolated C. concisus from three children with IBD (two with CD and one with UC) but not from any of the controls; however, based on PCR, the prevalences of C. concisus were not significantly different between patients and controls (92).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 94%
See 1 more Smart Citation
“…Up to 1% of the population in developed countries is diagnosed with acute campylobacteriosis each year, with the incidence of disease estimated to be even higher in developing nations (9,38,73). Human infection with C. jejuni causes severe watery to bloody diarrhea, abdominal cramps, and fever (9) and can also lead to more serious secondary sequelae such as GuillainBarré syndrome and inflammatory bowel disease (10,34,49,87). Despite its prevalence, much less is known about the pathogenesis mechanisms of C. jejuni compared to other enterics, such as Salmonella spp.…”
mentioning
confidence: 99%